Evaluation of Water Losses in Banias Water Network Using Water Audit Software - عبدالرحمن عباس; سلمان جميلة (Latakia University Journal -Engineering Sciences Series, 2021)
Water resources are under increasing demand, especially in recent years, for many reasons including climate change, population growth, and economic development. At the same time, there is a high rate of losses in the water networks, according to the World Bank 2006 study, about 32 billion cubic meters are "leakage", while only 16 billion cubic meters reach the consumer. Therefore, before looking for new alternatives to supply water, it is worth looking at reducing the water losses, especially since there are huge amounts wasted from the networks. This research deals with the problem of water losses and determines their quantity, as they constitute the most important challenges faced by water companies, In order to achieve this, the amount of produced water "produced" was measured in the city of Banias, in addition to collecting data on the amount of water consumed. “consumed water” and the so-called" unauthorized consumption" for the year 2018. In conclusion, the research evaluated the amount of water loses in Banias city by relying on the Water Audit Software program, and analyze it to its main components, real and apparent loss, as the total losses reached 65%, of which 43% are real losses and 22 % apparent losses.